2009
DOI: 10.22302/iccri.jur.pelitaperkebunan.v25i3.113
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cocoa Natural Resistancy to Cocoa Pod Borer by Silica Application

Abstract: Cocoa (Theobroma cacao L.) like most tropical trees is recalcitrant in tissue culture. Somatic embryogenesis is generally efficient micropropagation technique to multiply elite material. However, Somatic embryogenesis in cocoa is difficult and this species is considered as recalcitrant. One of the factors often considered as a component of in vitro recalsitrance is a high phenolic content and oxidation of these compounds. In cocoa tissue culture accumulate large amounts of poliphenolics compounds which probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is likely that cocoa can also benefit from the presence of Si in its biomass (Heckmam 2013). A study in Indonesia by Wijaya et al (2009) indicated that the pods on cocoa trees treated with Si were not attacked by pod borers, and may be attributed to their having Si, resulting in being harder than they otherwise were and therefore difficult to penetrate. The uptake of Si had improved cocoa growth significantly.…”
Section: Basalt Application To Improve Soil Productivity For Growing mentioning
confidence: 99%
“…It is likely that cocoa can also benefit from the presence of Si in its biomass (Heckmam 2013). A study in Indonesia by Wijaya et al (2009) indicated that the pods on cocoa trees treated with Si were not attacked by pod borers, and may be attributed to their having Si, resulting in being harder than they otherwise were and therefore difficult to penetrate. The uptake of Si had improved cocoa growth significantly.…”
Section: Basalt Application To Improve Soil Productivity For Growing mentioning
confidence: 99%
“…The presence of sufficient Si in the plant system may possibly prevent the outbreak of a cocoa disease. A study in Indonesia by Wijaya et al (2009) indicated that the pods on cocoa trees treated with Si was not attacked by borers. This may be attributed to them having Si that resulted in being harder than they otherwise were; thus, the pods were difficult to penetrate.…”
Section: Cocoa Growth and Productionmentioning
confidence: 99%
“…However, this type of control is considered to be environmentally unfriendly. By other means, CPB can be controlled by implementing good agricultural practices, such as sanitation of infested pods, frequent harvest, pod sleeving [1], use tolerant clones [6,7], inducing resistance [8], sex pheromones [9,10], phytocoater [11] and applying entomopathogen, such as Paecilomyces fumosoroseus [12], Beauveria bassiana [13] and Bacillus thuringiensis [14,15].…”
Section: Introductionmentioning
confidence: 99%